Strategies to Reduce the Door-to-Device Time in ST-Elevation Myocardial Infarction Patients - Salarifar, Mojtaba (J Tehran Heart Cent, 2019)
Background: Performing primary percutaneous coronary intervention (PPCI) in a timely fashion is a crucial part of the management of ST-elevation myocardial infarction (STEMI). We aimed to evaluate the contributing factors to and the etiologies of a prolonged door-to-device (D2D) time. Methods: In 2016, the D2D time was measured in all patients who were treated with PPCI at Tehran Hear Center. The major causes of a prolonged D2D time (>90 min) were determined. The second phase was then started in 2017 by focusing on the determined causes, and direct feedback was given to anyone having contributed to the delayed D2D time. The D2D time was compared between these 2 years. Results: The mean age of the patients was 59.54±11.82 years, and 82.2% of them were men. The median D2D time decreased from 55 minutes (IQR(25-75%): 40–82) in 2016 to 46 minutes (IQR(25-75%): 34–70) in 2017 (P<0.001). In the first year, 79.8% of the patients had a D2D time of below 90 minutes; the figure rose to 84.1% of the patients in the second year (P=0.017). The first cause of a prolonged D2D time was missed ST-elevation in the first electrocardiogram by physician or nurse (8.4% of the cases). Along with a declining rate of missed STE to 6.7%, the median D2D time in the missed patients also decreased from 205 minutes to 177 minutes (P=0.011). The rate of ambulance arrival increased from 10.2% to 20.7% of the cases, and the median D2D time also declined from 45 (IQR(25-75%): 34–55) to 34 (IQR(25-75%): 25–55) in these patients (P<0.001). Conclusion: Even in the setting of a 24/7 on-site interventionist in the hospital, the dispatch system and prehospital electrocardiograms, along with regular assessment and feedback, may improve the D2D time.